2015
DOI: 10.4236/ojo.2015.510044
|View full text |Cite
|
Sign up to set email alerts
|

Children Flat Foot and Lower Limb Rotational Profile: A Cross-Sectional Descriptive Study

Abstract: Flat foot in children is a common deformation, which appears during the first years of life. It requires a rigorous evaluation to rule out congenital or neurological abnormality. It is characterized by a decrease of the plantar concavity indeed collapse of the foot, often associated with other morphostatic deformations. The aim of this study is to find a correlation between the essential flat foot in children and lower limb disorders torsional. It is a cross-sectional descriptive study, recruiting 110 children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Noteworthy, FFF and rigid FF were 13.86% and 1.22%, respectively, and accounted for 91.94% and 8.06% of the positive cases, respectively, so we were close to Ali et al [27], who found the prevalence of FFF in Pakistani children was 89.6%, and prevalence of rigid FF was 10.4% of flat foot cases. Sonia et al [28] in their study of Tunisian children and Ezema et al [29] in their study of Nigerian primary school students found bilateral FF prevalence in flat foot cases was 75% and 91.5%, whereas bilateral FF was present in 90.8% of our flat foot cases. We demonstrated that the prevalence of pes cavus was 0.23%; this was in the vicinity with Bafor and Chibuzom [30], Chou et al [31], Yoosefinejad and Ghalamghash [32], and Bogut et al [21], who found that the prevalence of pes cavus in children was 0.7%, 1.32%, 2.5%, and 3.68% respectively.…”
Section: Discussionmentioning
confidence: 41%
“…Noteworthy, FFF and rigid FF were 13.86% and 1.22%, respectively, and accounted for 91.94% and 8.06% of the positive cases, respectively, so we were close to Ali et al [27], who found the prevalence of FFF in Pakistani children was 89.6%, and prevalence of rigid FF was 10.4% of flat foot cases. Sonia et al [28] in their study of Tunisian children and Ezema et al [29] in their study of Nigerian primary school students found bilateral FF prevalence in flat foot cases was 75% and 91.5%, whereas bilateral FF was present in 90.8% of our flat foot cases. We demonstrated that the prevalence of pes cavus was 0.23%; this was in the vicinity with Bafor and Chibuzom [30], Chou et al [31], Yoosefinejad and Ghalamghash [32], and Bogut et al [21], who found that the prevalence of pes cavus in children was 0.7%, 1.32%, 2.5%, and 3.68% respectively.…”
Section: Discussionmentioning
confidence: 41%
“…The largest sample was found in the paper written by Mueller et al (2016), 7575 participants, and the smallest number in the paper by Mickle, Cliff, Munro, Okely, & Steele (2011), 33 participants. Nineteen studies included participants of both genders (Pfeiffer et al, 2006;Mihajlović, Šolaja, & Petrović, 2010;Chen, Chung, & Wang, 2009;Chen, et al 2011;Mickle et al, 2011, Mickle, Steele, & Munro, 2006bHsun-Wen et al, 2012;Stanišić, Đorđević, & Maksimović, 2014;Sonia et al, 2015;Ezema, Abaraogu, & Okafor, 2014; Jiménez-Ormeño, Aguado, Delgado-Abellán, Mecerreyes, & Alegre, 2013; Woźniacka, Bac, Matusik, Szczygieł, & Ciszek, 2013;Riddiford-Harland, Steele, & Baur, 2011a;Mauch, Grau, Krauss, I., Maiwald, & Horstmann, 2008;Mueller, Carlsohn, Mueller, Baur, & Mayer, 2016;Echarri & Forriol, 2003;Vergara-Amador, Sanchez, Posada, Molano, & Guevara, 2012). One study included female participants (Mihajlović, Smajić, & Sente, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the authors in the analyzed papers measured and focused only on deformities of the longitudinal arch of the foot. Some authors, in addition to determining the status of the longitudinal arch of the foot, also analyzed the pes transverse planus (Mihajlović, Smajić, & Sente, 2010), feet insufficiency with the valgus position (Mickle et al, 2011;Mihajlović, Smajić, & Sente, 2010;Ezema et al, 2014), the state of the lower leg and hip and knee joint (Stanišić et al, 2014;Sonia et al, 2015). "Hollow feet" were analyzed by Woźniacka et al (2013) who obtained results which are contrary to one of the rules of flat feet, which is that with age the percentage of children with flat feet decreases, as in this case an increase in the prevalence of pes cavus was noted among older children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This discrepancy may be attributed to the distinct biomechanical demands between standing and walking. While the shape of the arch during standing is primarily dictated by bone structure, along with the strength and flexibility of ligaments [47], walking engages foot muscles to stabilize the foot [48]. In cases of flatfeet, altered structural characteristics and properties of ligaments may fail to adequately support the foot during relaxed standing.…”
Section: Footwear and Movementmentioning
confidence: 99%